Permanent Access to the Records of Science - The International Role of the e-Depot at the Koninklijke Bibliotheek, National Library of the Netherlands - van Trier, Gerard (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
In 1994 the Koninklijke Bibliotheek (KB) decided to include electronic publications in its deposit collection. This was considered as a logical extension of the deposit for printed publications already in place. In December 2002, after a few years of experimenting, the current e-Depot was delivered, with the IBM Digital Information and Archiving System (DIAS) as its technical 'heart'. The e-Depot is now fully operational and imbedded in the KB organisation. The emergence of the electronic journal creates new challenges to the traditional deposit model. Because of the involvement of international publishers of Dutch origin, the e-Depot has had an international dimension right from the start. In 2002 the KB signed an historic electronic archiving agreement with Elsevier Science, which covered the entire set of Elsevier journals. This arrangement turned the KB into the first official digital archive in the world for journals published by international scientific publishers. A year later the KB concluded a similar agreement with Kluwer Academic Publishers. Other publishers followed, also from outside the Netherlands: Biomed Central, Blackwell, Oxford University Press, Taylor and Francis, Sage, Springer and Brill Academic Publishers. On the basis of these agreements the e-Depot will eventually hold 9 million articles. The annual increase in the number of articles from these publishers will be around 400,000. Publishers are required to deposit their publications free of charge. Access is restricted: only on-site, for any registered user of the KB. Remote access is only offered with permission of the publisher. On-site retrieval, access, printing, downloading is for private use only, systematic reproduction is not allowed. Documents are available for interlibrary document supply within the Netherlands. The archive serves as a guarantee to all licensees worldwide. In case of calamities or in case the publisher does not meet his obligations, the KB safeguards the access that licensees have paid for. Primarily, long-term preservation is a way of managing risk and a kind of insurance against loss or disrupted access. The KB expects that worldwide permanent archiving of STM literature will be taken care of by a limited number of institutions dedicated to this task (Safe Places Model). Libraries should invest in a qualified archiving solution and should effectively demand archival deposit by publishers as a condition of licensing electronic journals. The KB’s e-Depot strategy for the coming years includes: • Further developing the technical and organisational infrastructure, which is now put to an external audit. • Continuing the Research & Development effort concentrating on the full range of available preservation techniques. The KB has developed its own R&D-programme and is an initiating partner in the European project PLANETS. • Concluding archiving agreements with more of the major international scientific publishers. The KB would like to reach 80% coverage of the total world production of STM literature. • Promoting the creation of a European infrastructure for long-term preservation and access to the records of science, including large scientific organisations like ESA, CERN and the British CCLRC, but also JISC, the European Science Foundation, the International Association of STM Publishers, and national libraries like The British Library and the KB. • Discussing the feasibility of new business models to cover the costs of storage space, the processing and management of the material, and R&D efforts.